Canales de búsqueda de empleo y duración del desempleo en el mercado laboral colombiano 2003 - Oviedo Gil, Yanira Marcela (Sociedad y Economía, 2007)
This investigation analyzes the labor intermediation in Colombia in 2003, examining what factors increases the propensity of the agents to use a particular job-search method and identifying the impact of its use in the duration of unemployment. The most efficient methods imply the active participation of who looks for.